In vitro cytotoxicity evaluation of green synthesized alumina nanoscales on different mammalian cell lines - Bukar, Alhaji Modu; Abdullah Jesse, Faez Firdaus; Che Abdullah, Che Azurahanim; M. Noordin, Mustapha; Z. Kyari, Modu; Norman, Ashreen; Mohd-Lila, Mohd Azmi (Springer Nature, 2024)
Nanoscale research is gaining interest in the biomedical, engineering, and environmental fields. Current expensive traditional chemical methods for synthesizing nanoparticles (NPs) inevitably lead to the synthesis of NPs with potentially less or no toxic effects on living cells. To overcome these challenges, in this study, we use a simple, inexpensive, and less toxic one-pot green chemistry approach instead of a chemical method to synthesize alumina nanoparticles (AlNPs) from Carica papaya extract. Nano-alumina has been widely studied due to its remarkable biological and physiochemical properties at nanoscale. However, to date, its biomedical application is limited due to the lack of sufficient data on cytotoxicity in living cells. The physicochemical properties of nano-alumina were determined by FT-IR, DLS, SEM and HRTEM. The cytotoxic effects of the synthesized nano-alumina were studied in cell lines LT and VERO at concentrations of 10–480 µg/mL in vitro. The cell viability of nano-alumina was evaluated using the MTT assay and the AO /EB double staining technique. Our results based on DLS and HRTEM analyzes confirmed spherical AlNPs with a zeta potential and average particle size of − 25 to 5 mV and 52 nm, respectively. The nano-alumina tested showed low toxicity to both cell lines after 28- and 48-h exposure. Furthermore, cell viability statistically decreased with increasing incubation time and concentration of AlNPs up to 480 μg/mL (p < 0.001). However, a minimal increase in cytotoxicity was observed at threshold levels in the range of 120–480 µg/mL. The half-maximal inhibitory concentration (IC50) of AlNPs in the VERO and LT cell lines were 153.3, 252.0 µg/mL and 186.6, 395.3 µg/mL, respectively, after 24- and 48-h exposure to AlNPs. Thus, we conclude that the cytotoxic effect of AlNPs depends on the concentration, exposure time and cell type. The result suggests that the concentration used in this study may be useful for biomedical applications.